2021
DOI: 10.1212/wnl.0000000000012753
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Disease-Modifying Therapies With COVID-19 Severity in Multiple Sclerosis

Abstract: Background:People with multiple sclerosis (MS) are a vulnerable group for severe COVID- 19, particularly those taking immunosuppressive disease-modifying therapies (DMTs). We examined the characteristics of COVID-19 severity in an international sample of people with MS.Methods:Data from 12 data-sources in 28 countries were aggregated (sources could include patients from 1-12 countries). Demographic (age, sex), clinical (MS-phenotype, disability), and DMT (untreated, alemtuzumab, cladribine, dimethyl-fumarate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
201
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(253 citation statements)
references
References 18 publications
(60 reference statements)
18
201
5
2
Order By: Relevance
“…During the last 20 years, scienti c progress led to the development of nearly 20 medications for MS therapy, including monoclonal antibodies targeting B cells via anti-CD20 (aCD20) such as rituximab or ocrelizumab 1 . aCD20 treated patients are at higher risk for hospitalization and a more severe course of COVID19 2 . Since the end of 2020, the rst vaccine candidates received emergency use authorization, showing high e cacy against SARS-CoV-2 infection 3 .…”
Section: Introductionmentioning
confidence: 99%
“…During the last 20 years, scienti c progress led to the development of nearly 20 medications for MS therapy, including monoclonal antibodies targeting B cells via anti-CD20 (aCD20) such as rituximab or ocrelizumab 1 . aCD20 treated patients are at higher risk for hospitalization and a more severe course of COVID19 2 . Since the end of 2020, the rst vaccine candidates received emergency use authorization, showing high e cacy against SARS-CoV-2 infection 3 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 3 An international cohort encompassing 1,683 confirmed COVID-19 cases in MS patients found that older age, progressive MS-phenotype, higher disability, comorbidities and anti-CD20 therapies were risk factors for a more severe course of COVID-19. 4 Other disease modifying therapies do not seem to carry an increased risk of a worse outcome of COVID-19 in MS patients. 1 4 Still, for all patients with MS, reaching protective immunity against SARS-CoV-2 is of utmost importance.…”
mentioning
confidence: 99%
“… 4 Other disease modifying therapies do not seem to carry an increased risk of a worse outcome of COVID-19 in MS patients. 1 4 Still, for all patients with MS, reaching protective immunity against SARS-CoV-2 is of utmost importance.…”
mentioning
confidence: 99%
“…Accumulating data suggest that treatment with anti-CD20 therapy, such as rituximab and ocrelizumab, puts patients at considerably increased risk of developing severe outcomes from COVID-19 (risk ratios ranging from 1·7 to 5·5 have been reported). 1 , 2 This reported risk emphasises how important it is that these patients develop protective immunity via COVID-19 vaccinations, but, unfortunately, studies have shown that humoral immune responses after COVID-19 vaccination are poor in patients with rheumatic diseases or multiple sclerosis who are taking anti-CD20 agents, even after two doses. 3 , 4 T-cell immunity after COVID-19 vaccination might be relatively unaffected by rituximab, but results from studies have varied, 5 , 6 and whether cellular immunity in the absence of humoral immunity provides sufficient protection against severe COVID-19 remains uncertain.…”
mentioning
confidence: 99%